Deterioration mechanisms of high-moisture wheat-based food – A review from physicochemical, structural, and molecular perspectives. (15th July 2020) - Ma, Meng; Sun, Qing-Jie; Li, Man; Zhu, Ke-Xue
Highlights: Overview of physicochemical changes in high moisture wheat products during storage. Changes in the main constituents of wheat products during storage were summarized. Physicochemical, structure, and molecule changes contribute closely to the deterioration. Abstract: Wheat-based products are staple foods for over a third of the world's population. However, most wheat-based staple foods are provided with a high water content to maintain naturally chewable mouthfeel, which leads to a short shelf life and limits their distribution and marketing. Understanding the fundamental mechanisms and dynamics that drive the quality deterioration is therefore essential for obtaining alternative technologies for optimal quality and extended shelf life. Here, we provide the basis for the physicochemical, structural, and molecular changes occurring in various wheat products during storage, intending to elucidate the underlying deterioration causes. Generally, more desirable qualities are obtained for fresh wheat products, both in appearance and mouthfeel. During storage, changes in the physicochemical properties, structure, main constituents, and water status contribute to the quality deterioration. Based on these changes, deterioration mechanisms are summarized to provide both theoretical and practical references for the quality regulation of high-moisture wheat-based food.